Efektivitas Pelayanan Ekspor Impor Pada Kantor Bea Cukai Dalam Upaya Mendukung Peningkatan Perekonomian Daerah (Studi Pada KKBC Tipe Madya Pabean C Cilacap) - Kristian Cahyandi (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2020)
Customs agency in Indonesia has an important role in procedural matters and in monitoring the entry and exit of goods from and to foreign countries. Customs agencies in carrying out their duties certainly face various obstacles and the right strategy is needed to overcome these obstacles. Tanjung Intan Cilacap Port is a trading gateway for the City of Cilacap and its surroundings, both local and export-import. The purpose of this study was to analyze the role of Customs and Excise in the effectiveness of export-import activities at the Tanjung Intan Cilacap port. This study uses a descriptive research method with a qualitative approach. Data collection methods used were unstructured interviews and documentation. The analytical method used in this research is the data analysis model of Miles and Huberman which includes the following steps, namely data reduction, data presentation, and drawing conclusions / verification and data analysis.